PLOTTING ENGEL CURVES FOR COMMODITIES "FOOD" AND "EDUCATION" IN THE CONTEXT OF UKRAINIAN HOUSEHOLDS’ WELL-BEING EVALUATION - Denys Verba; Alevtyna Kudinova; Olena Tkachenko; Andrii Samiilenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
The article is devoted to the adaptation of Engel's curve tools for evaluating the well-being of Ukrainian households. In particular, the assessment of the welfare inequality, observed between households with the lowest equivalent per capita income and the most affluent households, as well as the main trends in the change of the consumption structure for the period 2014-2020. The research is based on the concept that overcoming the concentration of consumer spending around the purchase of food is a necessary condition for the launch of microeconomic mechanisms of socio-economic development because it allows households to actively invest in the accumulation of human capital and thus overcomes the monopoly of budget financing of social sphere industries. To assess the level of satisfaction with food needs, the Engel line "income - food consumption" was constructed and the coefficient of elasticity of food consumption from income was determined. Similar calculations were made concerning the consumption of goods created by the educational sector. According to the results of the Engel function development, the income elasticity of the absolute amount of food consumption is equal to 0.47: an additional percentage of income encourages households to increase the amount of food consumption by 0.47%. According to our calculations, the income elasticity of educational goods consumption is equal to 0.928 (an additional percentage of real income encourages Ukrainian households to increase the amount of educational goods consumption by 0.93%). Therefore, Ukrainian households value education enough and tend to use economic opportunities (income released from priority needs satisfaction) for expanding education consumption. Both assessments of elasticity coefficients indicate that the achieved level of meeting food needs for the vast majority of Ukrainian households does not allow them to count on the release of their funds from meeting basic current needs and the expansion of those expenses that have the character of investing in human capital and have a pronounced positive impact on the qualification level of labor resources and the productivity of their use in the national economy.